Cybercrime: criminal threats from cyberspace - Brenner, Susan W. (Crime, media, and popular culture, 2010)
21st century twilight zone : stalking a town -- From mainframes to metaverse : the origins and evolution of cybercrime -- Three categories -- Target cybercrimes : hacking, malware, etc -- Tool cybercrimes : fraud, harassment-- murder? -- Cyber-CSI : computer crime scene -- Beyond war games : who are the cybercriminals? -- Cyber-law and order : investigating and prosecuting cybercrime -- U.S. law enforcement : agencies and challenges -- Global law enforcement : fewer agencies, even more challenges -- Privacy versus security : which trumps? -- What is the future of cybercrime?